Asynchronous Virtual Education Acceptance of University Faculty During Covid-19 - Vaca-Cárdenas, Mónica Elva; Ordoñez-Avila, Ermenson Ricardo; Gabriele, Lorella; Vaca-Cárdenas, Leticia Azucena (Journal of Ecohumanism, 2024)
Due to COVID-19, education has been blocked out on a global scale. Most countries around the world stopped educational activities and moved to virtual education. Even though most teachers and students were not prepared, they had to execute this unexpected change. Therefore, the purpose of this research was to measure the Asynchronous Virtual Education Acceptance of university faculty during the COVID-19 pandemic period. An Asynchronous Virtual Education Acceptance Scale for Faculty was designed and validated, which is an adapted version of the TAMPST (Technology Acceptance Measure for Preservice Teachers) questionnaire. A sample of 222 faculty of a public university in the coastal region of Ecuador responded to 28 technology items. The main results showed 75 percent of Faculty acceptance toward Asynchronous Virtual Education with strong correlations between the questions and their factors. It is concluded that training and previous use of the Virtual Platform helped to achieve this acceptance.